Impact of Thrombophilia Testing on Clinical Management: A Retrospective Cohort Study - McRae, Hannah L.; Müller, Jens; Rühl, Heiko; Pötzsch, Bernd (Hämostaseologie, 2024)
Thrombophilia management is based on the personal and family history of thrombosis. Current guidelines recommend performing thrombophilia testing only when the results will change clinical management. To investigate to what extent treatment recommendations changed following thrombophilia testing, clinical and laboratory data of 255 patients with and without venous thromboembolism who underwent thrombophilia screening were assessed retrospectively. A local score based on clinical indicators for thrombophilia was used to assess the pretest probability of thrombophilia. A total of 144 patients (57.6%) were found to have a clear thrombophilic phenotype, of which 78 were predicted to have definite thrombophilia and considered for indefinite anticoagulation; 66 were likely to have thrombophilia and were considered for indefinite or prolonged anticoagulation. Eighty-three (32.5%) could not be clearly classified and 28 (11%) were asymptomatic. A thrombophilic risk factor was diagnosed in 98 (38.4%) patients; this included 64 of 144 (44.5%) patients with a clear thrombophilic phenotype and 26 of 83 (31.3%) patients who could not be easily classified. Treatment recommendations changed in 57 of 255 (22%) patients following thrombophilia testing. Eight patients were switched from direct oral anticoagulants to vitamin K antagonists due to confirmed triple-positive antiphospholipid syndrome. In 49 patients, the anticoagulant dose was either increased (n = 3) or treatment was prolonged (n = 46) following diagnosis of high-risk thrombophilia. Clinically, assessing thrombophilia probability score before thrombophilia testing improves thrombophilia management recommendations.
Keywords: risk assessment; thrombophilia; anticoagulation therapy; thrombophilia testing